Gagak Hitam: A poem - Neong, Chee Kein (Arthur) (SARE: Southeast Asian Review of English, 2025)
This poem is a Malay-English hybrid poem, predominantly in the Malay language, from the point of view of a crow in Malaysia, a so-called Malaysian. A line-by-line English translation has been provided for the Malay words, unless it sounds better to include or exclude certain parts, in which case (artistic) liberty has been taken and the lines do not match, though this is rare. Certain words have not been translated where the translation has been given in the original poem itself. This poem attempts to characterise the crow’s misgivings about humans in general, while at the same time lending itself some human qualities. Perhaps this crow may even be misanthropic in nature, though in manner and in scale, no more destructive (if not less) than humans. It can be argued that the crow, in highlighting its desire to add layers of meaning to its name, is also revealing its secret wish and intentions, in the way that humans too have desires.